The Role of the Al-Iman Jayapura Mosque Management as Moral Educators in Fostering Noble Character - Nor Hadi; Wakib Kurniawan (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This study aims to describe and examine the role of the administrators of Al-Iman Mosque in Jayapura in promoting the development of positive character among mosque-affiliated youth. The research adopts a descriptive qualitative approach, employing data collection techniques such as in-depth interviews, participant observation, and documentation. The participants in this study consisted of four mosque administrators and ten youth members of Al-Iman Mosque in Jayapura. Data analysis was conducted through four stages: data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that mosque administrators play three key roles in fostering the moral development (akhlaq) of youth, namely serving as moral role models, acting as facilitators of religious and social activities, and functioning as motivators who provide guidance and spiritual support tailored to the needs of young people. This guidance is delivered through consistent religious education (regular study circles), worship training, participation in social and religious activities, moral mentorship, and the application of Islamic practices in daily life. Factors contributing to the effectiveness of this guidance include the presence of a religious mosque environment, strong community support, and close emotional bonds between administrators and youth. Identified challenges include limited participation among some youth, the negative influence of digital media, and insufficient mentoring resources. The study concludes that the administrators of Al-Iman Mosque make a significant contribution to fostering the moral development of youth within the multicultural context of Jayapura. This research highlights the importance of strengthening character-building programs based on role modeling, dialogue, and social engagement to support the development of moral values among contemporary youth.